![Pending changes are displayed on this page Pending changes are displayed on this page](/w/extensions/FlaggedRevs/frontend/modules/img/1.png)
There are no approved revisions of this page, so it may
not have been
reviewed.
This article page is a stub, please help by expanding it.
Indefinite summation (for discrete variables) is the equivalent of indefinite integration (for continuous variables.)
The indefinite summation of a discrete function (or sequence)
is
![{\displaystyle \Delta ^{-1}a(n)\equiv A(n)+C,\quad \Delta (A(n)+C)=A(n+1)-A(n)=a(n),\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/e300c22585b8303da640ac235e19e025a107a932)
where
is the indefinite summation operator,
is the forward difference operator and
if the indefinite summation constant.
Example
With
![{\displaystyle a(n)=n\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/8d357a0b250ea16f0ee13dde551b4e0a198f3c2c)
we get
![{\displaystyle \Delta ^{-1}a(n)=\Delta ^{-1}n={\frac {(n-1)n}{2}}+C=A(n)+C\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/6a426a09feddfd8f699bc3a1d6adb1e9a8d02ca9)
so that
![{\displaystyle \Delta (A(n)+C)=\Delta {\bigg [}{\frac {(n-1)n}{2}}+C{\bigg ]}={\bigg [}{\frac {(n-1)n}{2}}+C{\bigg ]}_{n+1}-{\bigg [}{\frac {(n-1)n}{2}}+C{\bigg ]}_{n}={\frac {n(n+1)}{2}}-{\frac {(n-1)n}{2}}=n=a(n)\,}](https://en.wikipedia.org/api/rest_v1/media/math/render/svg/cb926be106030e2b718994a7821ba7ca9eccbe76)
See also